LEGISLASI DAN PERUBAHAN IKLIM - Salim, Emil (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
The world is facing a crucial issue of climate change, whichsince 1992 is to be tackled through the UN Framework ofConvention on Climate Change. Its implementation till todayproves to be unsatisfactory. Conventional development hasfailed to cope with climate change issues. The need emerges tofollow a different path of development: sustainable developmentembracing simultaneously economic, social and environmentalsustainability pursued on the low-carbon growth path to reachfor the Millennium Development Goals.Indonesia is also committed to sustainable development inaccordance to the amended Constitution 1945 and its derivativesthat have been promulgated during the last decade. Thelegislation of laws and regulations in Indonesia suffers howeverserious institutional failures that has to be dealt with in thenear future. A more appropriate institution for legislation iscalled for to improve the effectiveness of Indonesian law makingin meeting the future challenges of the nation and the globe aswell.